2021
DOI: 10.1055/a-1346-5504
|View full text |Cite
|
Sign up to set email alerts
|

Risikoabschätzung einer akuten Exazerbation bei COPD-Patienten im Rahmen einer pneumologischen Anschluss-Rehabilitation anhand der Prävalenz und Schwergradausprägung von Komorbiditäten

Abstract: Zusammenfassung Einleitung Akute COPD-Exazerbationen (AECOPD) im Rahmen einer pneumologischen Rehabilitation (PR) sind häufige und gefährliche Komplikationen. Neben Einschränkungen der Lebensqualität führen sie zu einem Unterbrechung der PR und gefährden den PR-Erfolg. Eine Abhängigkeit zwischen dem Krankheitsstatus und einem erhöhten Risiko für eine AECOPD ist beschrieben. Dabei stellt sich die Frage, ob der Charlson Comorbidity Index (CCI) oder die Cumulative Illness Rating Scale (CIRS) dafür geeig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…22 P Luu et al also found that the risk of acute exacerbation significantly increased in COPD patients with higher CCI. 23 These results are consistent with our findings that the risk of readmission will increase by 1.304 times for every CCI point increase. COPD patients with frailty usually have other comorbidities and are in a high-burden state, increasing the risk of acute exacerbation, hospitalization, and death.…”
Section: Discussionsupporting
confidence: 92%
“…22 P Luu et al also found that the risk of acute exacerbation significantly increased in COPD patients with higher CCI. 23 These results are consistent with our findings that the risk of readmission will increase by 1.304 times for every CCI point increase. COPD patients with frailty usually have other comorbidities and are in a high-burden state, increasing the risk of acute exacerbation, hospitalization, and death.…”
Section: Discussionsupporting
confidence: 92%